ANALISIS SEISMISITAS SULAWESI BARAT BERDASARKAN DATA GEMPA 1967-2021 - Fajriani; Ihsan; Wahyuni, Ayusari (SAINFIS: Jurnal Sains Fisika, 2022)
The study aims to know level of seismicity, the level of rock fragility and the level of disaster risk in West Sulawesi. The data of earthquake used is secondary data in 1967 to 2021 obtained from BMKG and the GFZ-POTSDAM site with data processing parameters consisting of coordinate point, depth, magnitude, and the time of occurrance. To determine the level of seismicity and the level of rock fragility it uses fractal method with software Matlab-Zmap. From that method, the level seismicity is obtained with a value range of 0,33 to 2,86 and the level of rock fragility is in the range of 0,337 to 0,812. The area that has the highest seismicity is the Region of III Mamasa with a value of 2,86 while the lowest is Region of II Majene with a value of 0,33. The highest level of rock fragility is the Region of III Mamasa with a value of 0,812 and the lowest is the Region of II Majene with a value of 0,337. The area that has the highest level of earthquake risk is Mamasa while the lowest is Polewali Mandar